Immune status changes in patients with phlegmon in the maxillofacial region relation with purulent process prevalence - N. G. Barannik; S. D. Varzhapetyan; A. V. Sidoryako; Yu. S. Karabinova (Zaporožskij Medicinskij Žurnal)
Introduction. Significant portion of patients with acute purulent-inflammatory diseases of the face and neck often has a pronounced secondary immunodeficiency. One manifestation of violation of protective functions in this group of patients are changes in the synthesis of interleukin blood. Knowledge about the of the immune changes in the early stages of the face and neck abscesses development can be used for choosing the right timely empirical therapy. However, the currently available data regarding immune abnormalities in this pathology are controversial. Perhaps this is due to the influence of geographical, environmental and socio-economic factors on the immune status of patients and the results of studies. Thus, to obtain an objective picture of the nature of changes in the body's defenses of patients with inflammatory processes of the face and neck, it is advisable to carry out the study of the state of immunity for each region separately, and that was the basis for this study